Activation and reactivity of epoxides on solid acid catalysts - Saikia, Lakshi; Satyarthi, J. K.; Srinivas, Darbha; Ratnasamy, P. (Journal of Catalysis, 2007)
The aminolysis of epoxides over novel solid catalysts (Bronsted-acidic SBA-15 functionalized with propylsulfonic acid and Lewis-acidic Ti-MCM-41) is reported. The acidic properties of these catalysts were determined by FTIR spectroscopy and temperature-programmed desorption of pyridine and NH3, respectively. The mesoporous solid acids of the present study are reusable and exhibit significantly higher catalytic activities than known catalysts for opening of the oxirane ring with nitrogen (aromatic and aliphatic amines)-containing and oxygen (alcohols)-containing nucleophiles. A range of beta-amino, alcohols with high regioselectivity and stereoselectivity were synthesized. Adsorption studies as well as the sigmoid shape of the conversion- versus-time plots show that the epoxide and amine compete for adsorption on the acidic sites (-SO3H or Ti4+) on the catalyst surface. Epoxide adsorption and activation on acid sites are the more critical processes. Catalytic activity decreases with increasing basicity of the amines and/or the alcohol, as well as the dielectric constant of the solvent. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aminolysis and alcoholysis of epoxides; beta-Amino alcohols; ring opening of epoxides; SBA-15 functionalized with propylsulfortic acid; Solid acids; Ti-MCM-41

Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Hydrolysis of vegetable oils and fats to fatty acids over solid acid catalysts - Satyarthi, J. K.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complexes exhibit high catalytic activity for hydrolysis of edible and non-edible vegetable oils and animal fat. In a batch reaction, complete conversion of vegetable oil triglycerides to fatty acids with selectivity greater than 73 wt% was obtained at temperatures as low as 463 K, autogenous pressure and with 5 wt% of catalyst. Catalytic activity of DMC was superior to Amberlyst (TM) 70, SAPO-11, H-beta, HY, MoO(x)/Al(2)O(3) and sulfated zirconia. Rates of hydrolysis were greatly enhanced when solvents (tetrahydrofuran or N,N-dimethylformamide), phase transfer agents (tetrapropyl ammonium bromide) and products (a mixture of mono-/diglycerides and fatty acids) or fatty acid was added to the feed. Surface hydrophobicity which enables high wettability and activation of glycerides on active, acidic sites of reusable DMC is attributed to be the major cause for its superior catalytic activity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Double-metal cyanide complex; Fat splitting; Fatty acids; Hydrolysis of vegetable oils and fats; solid acid catalyst